Going Local DECENTRALIZATION, DEMOCRATIZATION, AND THE PROMISE OF GOOD GOVERNANCE - Merilee S. Grindle (PRINCETON UNIVERSITY PRESS PRINCETON AND OXFORD, 2007)
SEVEN PEOPLE played a vital part in making this book possibleâ€”the researchers who spent the summer of 2004 in thirty different municipalities in Mexico, asking questions, visiting project sites, seeking information, and observing processes of local governance. I owe an enormous debt of gratitude to them and the spirit of commitment and inquiry they brought to the fieldwork. Orazio Bellettini, Karla Breceda, Alexi Canaday-Jarrix, Elizabeth Coombs, XoÂ´ chitl LeoÂ´ n, and Alberto Saracho-MartÄ±Â´nez, graduates of the Kennedy School of Government at Harvard University, and Sergio CaÂ´rdenas-Denham, of the Harvard Graduate School of Education, worked long hours, generated important insights, shared their ideas with each other and with me, and persevered in sometimes difficult situations to generate the data on which this book is based. They also read the draft manuscript with care and insight, correcting errors and adding perspective. When we met at workshops, their excitement and good spirits about the project and what they were finding out was infectious. When I visited them in their field sites, they did their utmost to educate me about â€œtheirâ€ municipalities. I thoroughly enjoyed working with them and appreciate how much they allowed me to learn. I hope they are pleased with the results of their hard work. Most important, I hope they will long remember the summer they spent â€œGoing Loco.â€